Prospects of croton membranaceus for prostate Health - Appiah, A.A.; Asomaning, W.A.; Oppong, I.V.; Duker-Eshun, G.; Clement, J.; Okine, L.K.N.; Achel, G.; Gyampo, O.; Adjei, S.; Nyarko, A.K.; Aboagye, F.A.; Edoh, D.A. (ACS Symposium Series, 2013)
Croton membranaceus is used by Ghanaian traditional medical practitioners in the treatment of benign prostatic hyperplasia (BPH). Preparations of the root of this plant have been observed to relieve symptoms of BPH and enhance urination without the accompanying difficulty. There are no observable adverse effects associated with the clinical use of preparations of C. membranaceus. While medicinal significance has generated scientific interest in the plant there is real concern relative to the longer tem availability of this indigenous plant in its natural habitat. The objective of this review is to highlight the prospects of C. membranaceus for prostate health. © 2013 American Chemical Society.
Keywords: croton membranaceus; prostate Health; Health